A review of the effects of azole compounds in fish and their possible involvement in masculinization of wild fish populations. (May 2015) - Matthiessen, Peter; Weltje, Lennart
Abstract Endocrine-mediated effects in fish populations have been widely documented. Most attention has been focused on feminization caused by estrogenic substances, but this paper reviews evidence for the effects of a group of fungicides and pharmaceuticals, the azoles, which have been reported to cause masculinization in fish. The paper considers information from laboratory studies on the effects of azole compounds on fish endocrinology, and on the potential existence of such effects in wild fish. The occurrence of some azoles in effluents and surface waters has also been briefly reviewed. Under laboratory conditions, many azoles are able to cause masculinization or defeminization in fish by inhibition of the P450 enzyme aromatase (CYP19). However, in no case where such effects have been observed in the field has a link been established with this group of substances. In most instances, other more convincing explanations have been proposed. Peak concentrations of some azoles in surface waters can approach those which, under continuous long-term exposure in the laboratory, might lead to some aromatase inhibition. However, available data on exposure and effects provide reassurance that the concentrations of azoles found in surface waters are too low to cause adverse effects in fish by interference with their endocrine system. Compared to the widespread observations of feminization and estrogenic effects in (male) fish, there are relatively few papers describing masculinization or defeminization in (female) wild fish populations, suggesting that this is quite a rare phenomenon. The significance of this result is emphasized by the fact that fish are among the best studied organisms in the environment.